Effect of Home based Parent Child Interaction Therapy for families Having Children with Disruptive Behavior Problems at Selected Community of Khurda, Odisha, India - Namita Barik; Kshirabdhi Tanaya (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Disruptive and inappropriate behaviors of children are actions that interfere with theinstructional, administrative or service functions of the organization and family or school. In the early livesof children the significant risk factors for occurrence of antisocial behavior and criminal activity are thepresence of oppositional and disruptive behaviors. Related to this concept ,current study was conducted withobjectives to identify the families having children with disruptive behavior problems ,to determine the effectof (parent child interactive therapy) PCIT on disruptive behavior level ,to find out the association betweendisruptive behavior of the children with selected demographic variable.Materials and Methods: A quasi –experimental study was carried out with total 40 number of samplesby using total enumeration sampling technique.The intervention was carried out under the guidance ofguide and experts.Each Individual was exposed to the therapy for duration of 1 hour,twice a week . ChildDirected Session 30 MIN and Parent Directed Session 30 mins. Total no.of 5 session was carried out. Aftercompletion of intervention ,changing behaviour was assessed by eyeberg scale.Result: Study concluded that in experimental group 90% children shown mild disruptive behavior and 10%children found moderate disruptive behavior before giving intervention , and after intervention 10% childrendid not show any disruptive behavior and ,90% children had mild disruptive behavior . And there wasstatistically significant association between disruptive behavior of children with type of family, education offather, education of mother .Conclusion: There was significant difference between the scores of pre-test and post -test level of disruptivebehavior of the children in experimental group as ’p’ value (0.025*) at 0.05 level of significant.